Young children retain fast mapped object labels better than shape, color, and texture words. - Holland, Amanda; Simpson, Andrew; Riggs, Kevin J. (Journal of Experimental Child Psychology, 2015)
We compared short- and long-term retention of fast mapped color, shape, and texture words as well as object labels. In an exposure session, 354 3- and 4-year-old children were shown a set of two familiar and three novel stimuli. One of the novel stimuli was labeled with a new object label, color, shape, or texture word. Retention of the mapping between the new word and the novel object or property was measured either 5 min or 1 week later. After 5 min, retention was significantly above chance in all conditions. However, after 1 week, only the mappings for object labels were retained above chance levels. Our findings suggest that fast mapped object labels are retained long term better than color, shape, and texture words. The results also highlight the importance of comparing short- and long-term retention when studying children’s word learning.